"Atrophic Kidney"–like Lesion: Clinicopathologic Series of 8 Cases Supporting a Benign Entity Distinct From Thyroid-like Follicular Carcinoma. (December 2018) - Herlitz, Leal; Hes, Ondrej; Michal, Michal; Tretiakova, Maria; Reyes-Múgica, Miguel; Nguyen, Jane K.; Troxell, Megan L.; Przybycin, Christopher G.; Magi-Galluzzi, Cristina; McKenney, Jesse K.
Abstract : Renal mass lesions with a follicular architecture resembling atrophic kidney have been described, but their distinction from thyroid-like follicular carcinoma of the kidney remains controversial. We collected 8 cases of this purported "atrophic kidney"–like lesion to fully describe their clinical and histologic spectrum, their possible etiology, and to discuss their distinction from other renal neoplasms. Eight total cases were identified with patient ages ranging from 9 to 48 years (mean: 29 y; median: 28.5 y). Four patients were female and 4 were male. The tumors were unifocal and size ranged from 1.6 to 4.9 cm (mean: 3.4 cm; median: 3.4 cm). All 8 tumors had a remarkably similar histology. Each was enveloped by a smooth muscle rich capsule and had an overall low power "follicular" architecture. The luminal spaces of the "follicles" (or cysts) contained eosinophilic secretions and the lining epithelium was often flattened and atrophic, but some had more rounded cells with a distinctive hobnail arrangement. Many cysts contained discohesive round cells floating within the eosinophilic material, and some contained small intraluminal tufts with features of markedly atrophic glomeruli. Periodic acid-Schiff stains highlighted basement membrane material extending into these glomerular-like tufts, and some contained small distinct capillaries surrounded by endothelial cells, interspersed mesangial-like cells, and rare surrounding podocyte-like cells, providing additional evidence for glomerulocystic structures. Scattered calcifications were present within cysts (or within cyst walls) in varying numbers and were characterized by 2 types: psammoma body–like or more amorphous deposits. The tissue between cystic glomeruli contained predominantly small atrophic tubular structures, but collagenized stroma and smaller collapsed glomeruli were also present. The 2 tumors from the oldest 2 patients (48 and 39 y) had a more striking degree of stromal hyalinization. Immunohistochemically, the cyst lining cells had a predominant WT-positive/PAX-8 negative/CK7-negative phenotype, while tubules were typically WT-1 negative/PAX-8 positive/CK7-positive. Upon comparison to a control group of 10 kidneys containing incidental non–mass-forming glomerulocystic change, the morphologic features and immunophenotype were identical. To date, no patient has had any recurrence or aggressive clinical behavior based on follow status in 7 of 8 cases (follow-up range: 9 to 168 mo; median: 24 mo; mean: 40 mo). In summary, we describe the clinicopathologic features of 8 unique, benign "atrophic kidney"–like lesions that may simply represent a non-neoplastic form of organizing tubular atrophy and glomerulocystic change, and emphasize their distinction from thyroid-like follicular carcinoma of the kidney.